Perioperative management of a patient with left ventricular dysfunction and anomalous coronary arteries - Jyotsna Bhargava; Rajeev Lochan Tiwari; Mona Bana; Akhil Agarwal (Wolters Kluwer Medknow Publications, 2016)
Anesthetic management of patients with coronary artery disease undergoing noncardiac surgery is quite challenging. Such patients are at increased risk of perioperative cardiac complications and death. We report an illustrative case of a 62-year-old male with ischemic heart disease and anomalous coronary arteries for obstructed paraumbilical hernia repair.